Wpływ efektywności kosztowej oraz organizacyjnej na konkurencyjność firmy - Tomasz Lechowicz (Studia i Materiały)
Cost optimization in the company in a way that is constantly increasing profits is one of the main objectives of management. Continuous development of technology and market changes, make the achievement of higher profits is becoming increasingly difficult. Companies must perform difficult tasks associated with the expectations of their market partners - customers and competition resulting from the action. Technological innovation has become essential elements of the business. Business people, entrepreneurs, and managers are faced with the problem of determining the tools to achieve success and avoid pitfalls to choose the wrong strategy.